2014
DOI: 10.1073/pnas.1309915111
|View full text |Cite
|
Sign up to set email alerts
|

Processing of microRNA primary transcripts requires heme in mammalian cells

Abstract: Significance MicroRNAs (miRNAs) have important functions in development and cell physiology. The vast majority of mature miRNAs are produced from primary transcripts of microRNAs (pri-miRNAs) by a multi-step pathway. The first step, cleavage of pri-miRNAs by the Microprocessor complex, is highly regulated but technically challenging to study. We have developed a robust method that faithfully measures pri-miRNA processing efficiency in live cells. Using this assay, we establish an essential function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 44 publications
5
72
0
Order By: Relevance
“…In addition, previous studies concluded that heme binds DGCR8 across its dimerization interface and that heme availability affects pri-miRNA processing both in vivo and in vitro (Faller et al 2007;Senturia et al 2010;Weitz et al 2014). …”
Section: Discussionmentioning
confidence: 98%
“…In addition, previous studies concluded that heme binds DGCR8 across its dimerization interface and that heme availability affects pri-miRNA processing both in vivo and in vitro (Faller et al 2007;Senturia et al 2010;Weitz et al 2014). …”
Section: Discussionmentioning
confidence: 98%
“…To test these possibilities, we resorted to a widely used in vivo reporter vector for pri-miRNA processing ( Fig. 2D; Mori et al 2014;Weitz et al 2014). Specifically, miRNA hairpins or their mutants were cloned into the 3 ′ UTR of mCherry in a dual GFP/mCherry vector so that pri-miRNA processing will destabilize mCherry mRNA, with more efficient processing leading to a higher ratio of GFP/ mCherry signals by flow cytometry (see example in Supplemental Fig.…”
Section: Systematic Comparison Of Hairpin Features For Mammalian Pri-mentioning
confidence: 99%
“…In the cytosolic compartment binding of miRNAs to target mRNAs interferes with translation or mRNA stability. A critical complex partner of DROSHA is DGCR8 (DiGeorge syndrome critical region gene 8 protein) which possesses a heme-binding domain relevant for substrate recognition (Quick-Cleveland et al, 2014;Weitz et al, 2014), and hence links mitochondrial iron supply via heme formation to the entire regulatory miRNA network (Fig. 4).…”
Section: Posttranscriptional Iron Regulation Involving Microrna-210 Amentioning
confidence: 99%